Pengembangan Media Pembelajaran Flashcard berbasis Etnopedagogi pada Pendidikan Pancasila di Madrasah Ibtidaiyah - Nabila, Aura; Rofi’ah, Siti (IBTIDA', 2024)
Pendidikan Pancasila has an important role in shaping students' national character and identity. In this context, the use of card media is able to visualize abstract concepts that are integrated with local wisdom in learning at Madrasah Ibtidaiyah and make learning more interesting and meaningful. This research aims to describe the results of flashcard media development and at the same time analyze the results of expert validation. This research method is development research with the development model used is the ADDIE model which has 5 stages, namely Analyze, Design, Develop, Implement, and Evaluate. The subjects in this study were class IV MI Darul Ulum Tapen. Data was collected through questionnaires from validators, media design experts and material experts as well as students. Data were analyzed using qualitative descriptive analysis. This development research produced a product in the form of flashcard based on ethnopedagogy as a learning medium. The results of material expert validatrs reached 82%, media design experts 90% and student responses 97.%. This shows that the flashcard media received a very suitable assessment for use in Pancasila learning on diversity material in class IV MI Darul Ulum Tapen Jombang.